Perception on the innovative characteristics of small and medium enterprises (SMEs) manufacturing firms in Peninsular Malaysia. - Yahya, A.Z.; Mail, R.; Othman, M.S.; Ibrahim, M.S. (2008)
The main purpose of the paper is to attempt to explore the perception on the innovative characteristics of SMEs manufacturing firms based on three dimensions of a business: strategy, process and ways of working (culture). A survey of 60 Peninsular Malaysia-based manufacturing SMEs was conducted. In this study, a definition of innovation was established based on past studies and a systematic approach to measure company innovativeness was adopted. Ten indicators were used to measure company innovativeness. The top 20 per cent firms were compared with bottom 80 per cent firms in terms of product innovation management, process and work organisation. Means of responses were compared for two sets of companies. Tests were performed to draw some conclusions on the results. The results showed that the characteristics of more innovative SMEs manufacturing firms are perceived to be different in 10 variables as compared to the less innovative SMEs manufacturing firms. Among the variables that vary are: use of CAD, use of CAM, employee suggestion scheme, commitment to innovation, provided training for managers.